Penanaman Nilai-Nilai Moderasi Beragama Di MIN-4 Paluta - Khoirul Amri Rambe; Muhammad Fauzan; Muhammad Ridwan; Dini Anjani; Indah Permata Sari; Tini Setiawati; Ira Rizkia Ningsih; Ami Rizkiana; Sakinah Maulidah (Jurnal Kabar Masyarakat, 2024)
As a form of community service, KKN STAIN MADINA held outreach regarding the understanding of Religious Moderation at MIN-4 PALUTA, Padang Garugur Village. This research was conducted to provide an understanding regarding religious moderation because the majority of students at Madrasah Ibtidaiyah Negeri-4 North Padang Lawas do not really know about religious moderation. Meanwhile, the research method used was a qualitative and descriptive approach. The results of research from religious moderation counseling at MIN 4 PALUTA are as follows: (1) Aqidah, (2) Worship, (3) Morals (4) Reading the Koran